Digital Marketing and Major Selection: How Persuasive Messages Spark Intrinsic Motivation - Ledyva Yolanda; Ari Prasetyoaji; Maryaningsih Maryaningsih (Universitas PGRI Yogyakarta, 2026)
This study investigates the impact of digital marketing persuasive messages on high school students' intrinsic motivation in major selection. While higher education institutions utilize aggressive digital campaigns focusing on extrinsic rewards, this research positions digital marketing as a psychological variable influencing career orientation stability. Using PLS-SEM, data were collected from 855 social-media-active students in Yogyakarta. The structural model demonstrates robust predictive power, explaining a substantial variance in decision paralysis (R2 = 0.615) and a moderate variance in intrinsic motivation (R2 = 0.428). The results reveal that high intensity of persuasive content and algorithmic exposure significantly trigger cognitive overload (β = 0.425 and β = 0.380, respectively), which directly precipitates decision paralysis (β = 0.680). This mental fatigue subsequently erodes intrinsic motivation (β = -0.310; direct path β = -0.150) and increases cognitive dissonance (β = 0.520). Critically, the findings demonstrate a significant negative overall effect (p<0.001), confirming that excessive, uniform digital marketing produces a destructive psychological cycle, replacing pure interest with anxiety and dependence on digital trends. The study concludes that universities must shift from quantity-focused strategies to more authentic, curated information to foster genuine student interest and reduce the risk of future academic burnout or dropout. Keywords: cognitive overload, decision paralysis, digital marketing, intrinsic motivation, major selection